Qualitative interviews of patients with COPD and muscle weakness enrolled in a clinical trial evaluating a new anabolic treatment: patient perspectives of disease experience, trial participation and outcome assessments - Maggie Tabberer; Nicola Williamson; Sophi Tatlock; Adam Gater; Rebecca Grimes; Chika Akinseye; David Neil; Aoife Mahon-Smith; Linda Nelsen (SpringerOpen, 2024)
Abstract Background Chronic obstructive pulmonary disease (COPD) and muscle weakness can cause impaired physical function, significantly impacting patients' health-related quality of life (HRQoL). Loss of muscle strength is usually assessed through clinical and performance outcome (PerfO) assessments, which consists of tasks performed in a standardized manner, providing evidence of a patient's functional ability. However, evidence documenting the patient experience of COPD and muscle weakness is limited. Methods This two-stage qualitative study used semi-structured interviews in patients aged 45-80 years with COPD (post-bronchodilator forced expiratory volume in 1s [FEV1]/forced vital capacity ratio < 0.70, and FEV1% predicted of 30-80%) and muscle weakness. In Stage 1, 30-minute concept elicitation interviews were conducted with participants recruited across three US sites to explore impacts on physical functioning and activities of daily living. In Stage 2, interviews were performed with participants exiting a Phase IIa trial investigating the efficacy of a selective androgen receptor modulator (GSK2881078) on leg strength, whereby PerfOs were used to evaluate strength and physical functioning endpoints. These participants completed either 60-minute in-depth (n = 32) or 15-minute confirmatory (n = 35) interviews exploring trial experience, completion of outcome measures, disease experience and treatment satisfaction. Results In Stage 1 (n = 20), most participants described their muscles as weak (83.3%). Difficulties with walking (100%) and lifting heavy objects (90%) were reported. In Stage 2, 60-minute interviews, all participants (n = 32) reported a positive trial experience. Most participants reported that the home exercise program was easy to fit into daily life (77.8%), the PROactive daily diary was easy to complete (100%) and wearable sensors were easy to use (65.6%). However, technical issues were reported (71%), and few participants (19.4%) found physical assessments easy to complete. Improvements in muscle strength and functional limitations were reported by most participants. The shorter 15-minute confirmatory interviews (n = 35) supported the in-depth interview results. Conclusion The qualitative interviews generated in-depth evidence of key concepts relevant to patients with COPD and muscle weakness and support the assessments of patient strength and physical function as outcome measures in this population in future studies. Trial number GSK Stage 1: 206869; Stage 2: 200182, NCT03359473; Registered December 2, 2017, https://clinicaltrials.gov/ct2/show/NCT03359473 .